The Communicative Behaviour of the Russian Intelligentsia and Its Reflection in Reviews, as a Genre, Published in Online Literary Journals Abroad (Филологический класс, 2015)
This article analyzes reviews published in online literary journals associated with the «Russian intelligentsia» as a social group. Using «construction grammar», it identifies the stable structural components of reviews as a genre that are important for communicating information and values, as well as the genre’s mobile structural components, that is, the functional-semantic types of speech. Through its analysis of these stable and mobile structures, it examines the influence of the Internet and virtual space on the language of reviews. This article describes the means of expression that constitute the communicative behaviour of reviewers, who — in a second level of reflection — are also viewed as representatives of the Russian intelligentsia. It identifies the important implicatures in the genre’s structure, which constitute the Weltanschauungen and values of this social group. This article highlights the importance of this research for teaching textual understanding and analysis.